Radiofrequency Intradiscal Biacuplasty for Treatment of Discogenic Lower Back Pain: A 12‐Month Follow‐Up. Issue 3 (23rd October 2014) - Kapural, Leonardo; Vrooman, Bruce; Sarwar, Sheryar; Krizanac‐Bengez, Ljiljana; Rauck, Richard; Gilmore, Christopher; North, James; Mekhail, Nagy
Abstract: Introduction: Discogenic low back pain (LBP) affects a considerable number of patients suffering from chronic LBP. Recently, a growing interest has emerged in minimally invasive treatment options for discogenic LBP. Intradiscal biacuplasty (IDB), which uses cooled radiofrequency technology to ablate nociceptors in the posterior aspect of the intervertebral disc, is one such option. We previously presented 6‐month results of a randomized, double‐blinded, sham‐controlled study. Now, we present the unblinded, 12‐month follow‐up data for treatment patients and 6‐month data for cross‐over subjects from the original sham group. Methods: Physical function, pain relief, and disability were assessed using the Short Form‐36, numerical rating scale, and Oswestry Disability Index, respectively. Subjects were unblinded at 6 months, and those initially randomized to sham procedure were given the option to cross over to IDB. Results: Twenty‐two out of 27 subjects in the original active treatment group were followed until 12 months and had clinically significant improvements in physical function (Δ = 22) and pain (Δ = −2.9). Out of 30 subjects originally in the sham group, 24 chose to cross over, and 20 cross‐over patients completed follow‐up at 6 months. In cross‐over patients, improvements in physical function and pain did not differ statistically from those of patients originally randomized to IDB treatment. No complications or adverse events related to the procedure were reported. Conclusions: Clinically significant improvements after IDB initially reported at 6 months were maintained at 9 and 12 months. The cross‐over subjects had similar improvement in all outcome measures at all observed time points.